Effective of Lemongrass (Cymbopogon citratus L.) Essential Oil Incorporated in Chitosan-Based Edible Coating to Extend Hen Egg Shelf-Life during Storage - N. P. Minh (Journal of Global Pharma Technology, 2016)
Hen egg is one of the finest foods, offering human a complete balance of essential nutrients with proteins, vitamins, minerals and fatty acids with huge biological value. Eggshells have been regarded as natural protective barriers of eggs. However, eggs encounter different problems, such as weight loss, interior quality deterioration, and microbial contamination. Chitosan has attracted much attention owing to its extraordinary performance such as well-forming, low gas permeability, biocompatibility, strong antimicrobial attributes. Our present research focused on the application of lemongrass (Cymbopogon citratus L.) essential oil incorporated in chitosan-based edible coating to extend egg shelf-life during storage. This research was conducted from 2018 to 2019 in the scientific laboratory of Soc Trang Nanotech Ltd. Results revealed that 0.4% lemongrass oil incorporated with chitosan 1.5% was appropriated to extend hen egg shelf-life for 8 weeks. Chitosan incorporated with lemongrass essential oil coating is considered an efficient and practical way to preserve eggs at room temperature.Keywords: Hen egg, Lemongrass essential oil, Chitosan, coating, Shelf-life, storage.